2018
DOI: 10.1007/s12519-018-0182-2
|View full text |Cite
|
Sign up to set email alerts
|

Leptin gene polymorphism affects leptin level in childhood asthma

Abstract: BackgroundLeptin may induce inflammation in asthma by activation of Th2 cells. It has also been demonstrated that leptin expression increases upon inflammation and that asthmatic patients show increased serum leptin levels. We hypothesized that the polymorphism in leptin (LEP) and leptin receptor (LEPR) genes is associated with childhood asthma and may affect their serum level. To our knowledge, there are no reports analyzing LEP and LEPR polymorphisms in association with their serum levels in childhood asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
(31 reference statements)
1
11
0
Order By: Relevance
“…Unfortunately, we had no data regarding allergic rhinitis, but we found no associations between adipokines and atopic sensitisation, in line with another study [13]. Higher levels of leptin in asthmatic vs non asthmatic children have been found in some studies [12,17,[28][29][30], but not in all [13]. Higher levels of leptin and lower levels of adiponectin have been found in children with allergic rhinitis compared to children without allergic rhinitis [31].…”
Section: Discussionsupporting
confidence: 81%
“…Unfortunately, we had no data regarding allergic rhinitis, but we found no associations between adipokines and atopic sensitisation, in line with another study [13]. Higher levels of leptin in asthmatic vs non asthmatic children have been found in some studies [12,17,[28][29][30], but not in all [13]. Higher levels of leptin and lower levels of adiponectin have been found in children with allergic rhinitis compared to children without allergic rhinitis [31].…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies suggested that IL-1β gene polymorphisms may constitute a risk factor for childhood atopic asthma or severity via influence on gene regulation leading to a altered protein serum level in atopic asthma or atopic dermatitis [24][25][26][27]. And although the serum leptin level is elevated by obesity, leptin and leptin receptor gene polymorphism is associated with higher serum leptin levels in asthma, and these 2 variables have a high predictive value for asthma risk [28,29]. To date, there were no data about the genetic polymorphisms of inflammasomes including IL-1β or leptin in AR.…”
Section: Discussionmentioning
confidence: 99%
“…It may also have a role in altering the lung function [58,62]. Finally, it has recently been described that the polymorphism rs13228377 of the leptin gene is associated with higher levels of leptin in serum in asthma and those two variables (polymorphism + elevation in leptin) have a high predictive value for asthma risk (OR = 17.5, predictive accuracy 83.9%), although the authors themselves recognise the limitation of the scant sample [64]. In addition, it has been described that the single nucleotide polymorphisms (SNPs) of the leptin and adiponectin genes have a protective effect for asthma, but that that effect is lost in obese individuals [65].…”
Section: The Role Of Adipokines and Insulin Resistancementioning
confidence: 99%